THE EARLY-MIDDLE TRIASSIC BOUNDARY AT CHIOS (GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The sections of Marathovouno hillock in Chios (Greece), proposed by Assereto (1974) as stratotype for the base of the Anisian, have been revisited. An additional new section, Parthenis, near the town of Chios, was also considered. The ammonoid fauna of the Late Spathian, fairly rich in the Parthenis secion, fully belongs to the Prohungarites/Subcolumbites zone, sensu Kummel (1973). Additional ammonoid collections have been made from the stratotype section of Assereto, as well from section G, where the Aegean Paradanubites has been found above the condensed horizon. In the Parthenis section the earliest Anisian is missing because of a sedimentation gap. Several post- Aegean ammonoids have been found in red limestones olistoliths within the Variegated Series (Bunte Serie). The conodonts gave a more continuous record troughout all the sections. The most significant species to be considered are; Neospathodus homeri, Gondolella timorensis and Gondolella regale. The first occurrence of G. timorensis overlaps the N. homeri range for more than 1 m in thickness, below the bed with the ammonoid Aegeiceras. G. regale seems to be never associated with N. homeri and, appears later than the typical Aegean ammonoid fauna. Microfacies analysis revealed the presence of long ranging foraminifers. As far as the base of the Anisian is concerned, we may advance the following statements. 1) The base of the stage may be traced with the FAD ol Aegeiceras, Paracrochordiceras, Paradanubites and Japonites. 2) The FAD of G. timorensis slightly preceeds the Aegean ammonoid FAD. Thus, if the boundary is drawn on the base of ammonoids, G. timorensis FAD is latest Spathian in age. 3) G. regale FAD occurs later than the Aegean ammonoid fauna FAD. By correlation to the Nevada Star Peak Canyon section, the Aegean fauna of Chios seems correlative to the Japonites welteri beds of Bucher (1989).
Keywords: Triassic; Anisian; Scythian; Greece; Biostratigraphy